Irrawaddy Mon Amour - Grignani, Nicola; Testagrossa, Valeria; Zambelli, Andrea (Italy, 2015)
Living under a repressive military regime is even more difficult for Myanmar’s LGBT citizens; homosexuality remains taboo, many face overt discrimination and condemnation, and same-sex marriage is illegal. Yet on the banks of the Irrawaddy River, a small, gay-friendly community goes against the rules and helps two young lovers realize their dream.
Verzio Film Festival Submission
Keywords: Documentary films